Модернизация колонкового набора со съемно-раздвижной коронкой - Онищин, В.П.; Меркулова, В.А.; Сибирляк, З.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The retractable core bit SRK-76 is the most famous Russian construction for drilling hard rock. It has not been used during long time and now there are conditions to modernize this system for effective work without put out operations of drilling equipment.